Analysis of Attitudes towards Curricular Innovation in Higher Education staff - Meneses, Galia; Balladares Hernández, Jaime; Navarro-Ibáñez, Martín (Límite (Arica), 2025)
Curricular innovation in higher education is essential for addressing academic and societal demands, however, its implementation depends significantly on faculty engagement. This study explores faculty attitudes toward curricular innovation, focusing on the interplay between personal factors, institutional support, and willingness to participate in these processes. Specifically, the study aims to identify the attitudes that promote or hinder curricular innovation, examine how personal factors such as professional background and experience influence these attitudes. Through a quantitative approach and a retrospective descriptive design, the study analysed the responses of 174 participants using a questionnaire with a Likert scale. The results show that the teaching staff shows a positive attitude toward innovation. However, the institution states that it does not provide them with prompt information nor favour their active role. The results highlight the need to include organisational and personal factors in the innovation processes to increase engagement and increase the likelihood of long-term change and continuous improvement. These findings contribute to broader discussions on enhancing institutional strategies for curricular development and innovation in higher education.